School buildings rehabilitation : indoor environmental quality and enclosure optimization /: indoor environmental quality and enclosure optimization. ([2015]) - Almeida, Ricardo M. S. F; Peixoto de Freitas, Vasco; Delgado, João M. P. Q
No abstract available